Insights of Collaborative Learning Approach from Social-Psychology Perspective: A Systematic Review - Sahril Nur; Ranta Butarbutar (UNIB Press, 2022)
Collaborative learning (CL) is a learning approach that emphasizes activities that are focused on the students. Interdependence, social behavior, cognitive development, and social psychology views may all be used to explain its effectiveness. The systematic review's purpose is to investigate effective influencing elements on CL insight from a social psychology perspective. The research was evaluated using a qualitative technique and then thematically analyzed. The findings break down the success of CL interactions into three categories: social cognition, social conduct, and connections. The social-psychological aspects of collaborative learning, according to our research, have also become an important component included in curricular practices. As a consequence, starting with pre-service and building on it with teacher professional development would be better. We suggest that in the twenty-first century, collaboration, rather than rivalry, is a power to survive, and vice versa.